200 V Fast Recovery Epitaxial Diode with superior ESD capability. (September 2016) - Irace, A.; Maresca, L.; Mirone, P.; Riccio, M.; Breglio, G.; Bellemo, L.; Carta, R.; Naretto, M.; El Baradai, N.; Para, I.; Di Santo, N.
Abstract: In this paper the Electrostatic Discharge (ESD) capability of 200 V Fast Recovery Epitaxial Diodes (FREDs) is analysed by means of suitable experiments, TCAD simulations and theoretical analyses. Different doping profiles are investigated in order to improve the ESD robustness of a standard device and an optimized doping profile is proposed. The newly fabricated devices show a remarkably high ESD capability without any significative loss in forward voltage drop and a reduction of the breakdown voltage that does not affect device rating. Highlights: FRED Power Diodes, 200 V rated, showed a reduced ESD capability. Impact ionization can lead to current filamentation during ESD. A buffer layer was introduced at the cathode side of the device. Static and dynamic performances were unchanged and ESD capability was increased.